Ornamen Rumah Adat Aceh Utara dalam Terminologi Arsitektur - novianti, yenny; Amalia, Lisna; Deni, Deni (Arsir, 2022)
Along with the times, Indonesian culture is starting to be neglected by various groups, especially the millennial generation. This can be seen in the erosion of culture in a region, especially in the values and meanings contained in carvings on the ornaments of traditional houses of north aceh, so that preservation is needed to inhibit the acceleration of the rate of shift in the value of modern society's life. Cultural preservation is also a process of preserving, maintaining and preserving culture so that the cultural meanings contained in it are maintained properly so as not to eliminate the original character of the culture itself. This study aims to reveal the existence of carvings on ornaments, their general meaning and meaning in architectural semiotics on carvings of traditional houses of Aceh Utara. The data analysis technique used in this research is architectural semiotics which was developed by Charles Jencks, namely signifier-signified which describes the interpretation of meaning, langue-parole which describes universal and individual linguistic meanings and syntagmatic-paradigmatic to analyze the relationship between language rules and rules in grammatical units in the form of carvings on the ornaments. The results and discussion found from this study are the traditional house of North Aceh using the Aceh Besar decorative motif as the basis for its later ornamental carvings which have gone through developments and modifications based on local cultural considerations. Besides that, North Aceh has the bungong mata uroe motif as the original motif from the region. Decorative motifs on ornamental carvings tell about the way of life, the philosophy of life, culture, mores and religion.